Controlled Release of Polyethyleneimine-Simvastatin Acid Nanoparticles from Conducting Matrices and Their Osteogenic Potential - Oungbho, Dr. Kwunchit (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of the present study was to develop polyethyleneimine-simvastatin acid nanoparticles (PEI-SVA-NPs) loaded conducting scaffolds as drug delivery for osteogenesis in bone tissue regeneration. Materials and Methods: The PEI-SVA-NPs were prepared by nanoprecipitation by mixing PEI and SVA solutions. The freeze-dried NPs were loaded at 0.1, 0.5, and 1 mg onto the conducting scaffolds comprising chitosan grafted polyaniline/chitosan-gelatin matrices for drug release, biocompatibility, and alkaline phosphatase (ALP) activity studies. Results and Discussion: The PEI-SVA-NPs loaded conducting matrices exhibited slower drug release profiles compared with the free drug ones. Biocompatibility of the matrices was excellent on MC3T3-E1 cells. The PEI-SVA-NPs loading showed higher efficacy on promotion of osteogenesis than the free drug loading. Increasing ALP activity was found with increasing the PEI-SVA-NPs loading. Conclusion: The PEI-SVA-NPs loaded conducting matrices exhibited controlled release, biocompatibility, and osteogenic properties. The results strongly support the possibility of these matrices to be useful for bone tissue engineering application.